Analisis pelaksanaan layanan konseling pranikah dalam meminimalisir perceraian di Kantor Urusan Agama Kambu Kota Kendari - Heti Juningsih; Khairunnisa Syamsu (Universitas Indraprasta PGRI, 2021)
This study aims to determine the pre-marital counseling guidance service (to minimizing divorce in KUA Kambu District, Kendari City. This study will analyze the role of religious instructors in minimizing divorce in KUA Kambu District, counseling guidance strategies in minimizing divorce in Kambu District KUA, and the constraints). the obstacles faced in carrying out premarital counseling guidance to avoid divorce at KUA District Kambu. This research is a descriptive qualitative approach. Data collected by in-depth interviews with resource persons, documentation studies, and direct observations related to the implementation of family counseling at the KUA Kambu District, Kendari City. as in KUA Kambu District, Kendari City.